Literacy and Education Movement to Increase Public Awareness of the Importance of Education in Buntu Bedimbar Village - Adi Suarman Situmorang; Novita Dwi Yanti Gulo; Yohanna Br Bukit; Asnita Fridawati Saragih; Lestari Sinaga; Lita Agnes Siburian; Yesi Yona Sihaloho (Indonesian Journal of Society Development, 2023)
This PKM activity aims to increase the literacy of children in Buntu Bedimbar village, especially problem solving in story problems, provide socialization about the awareness of the Buntu Bedimbar community of the importance of education for their children, and to increase children's learning motivation around Buntu Bedimbar Village. As for the results obtained from the activity, when carrying out or carrying out activities, there are obstacles and problems, but all of them can be overcome so that every program implemented is well received, and the community also really helps us in running the PkM program. Another result obtained is the increased learning motivation of children around Buntu Bedimbar Village